Linking Periodontitis to Adverse Pregnancy Outcomes: a Comprehensive Review and Meta‑analysis (2024)
ABSTRACT: Purpose of Review Numerous investigations have explored the potential link between periodontitis and low birth weight (LBW) as well as preterm birth (PTB). However, the evidence remains inconclusive. Bacteria, their by-products, and proinflammatory cytokines originating from periodontal tissues can reach the placenta, inducing inflammatory changes that may contribute to pregnancy complications. Recent Findings A total of 35 studies involving 2,510,556 women were analyzed. The quality of the studies varied, but the meta-analysis consistently showed a moderate association between periodontitis and low birth weight. The observed association between periodontitis and low birth weight was moderate (OR 2.48; 95% CI 1.72–3.59), and it became even stronger when analyzing case–control studies independently (OR 3.94; 95% CI 1.95–7.96). On the other hand, the association between periodontitis and preterm birth was weak (OR 1.87; 95% CI 1.57–2.22) with highly significant heterogeneity. However, the presence of high heterogeneity and publication bias in the studies casts some limitations on the confidence in the results. Summary The available evidence, albeit of low quality, supports a moderate association between periodontitis and low birth weight, as well as a weak association with preterm delivery. Nonetheless, these findings must be interpreted cautiously, given the limited confidence in the effect estimates due to potential biases and heterogeneity in the studies.